Welfare Effects of Fiscal Policy under Alternative Exchange Rate Regimes : The Role of the Scale Variable of Money Demand - Ingo Pitterle; Dirk Steffen (Eberhard Karls Universität Tübingen, Wirtschaftswissenschaftliche Fakultät, 2004)
This paper investigates the implications of alternative scale variables of money demand for the comparison of a flexible exchange rate regime with a monetary union in a NOEM setup. The welfare evaluation of exchange rate regimes depends on the exchange rate response under the flexible regime. When the scale variable is private consumption, a domestic fiscal expansion yields a depreciation. As the associated expenditure switching and terms-of-trade effects are beneficial to the domestic country, households prefer flexible exchange rates. However, when the scale variable is total absorption, we obtain an appreciation and the welfare results are reversed.
urn:nbn:de:bsz:21-opus-18244
Keywords: F31; F42; F32; F41; 330; Fiscal Policy; New Open Economy Macroeconomics; Money Demand Specification; Flexible Exchange Rates; Monetary Union; Pricing-to-Market; Finanzpolitik; Wechselkurssystem; Neue Makroökonomik offener Volkswirtschaften; Geldnachfrage; Wohlfahrtseffekt; Währungsunion; Theorie